`2/3x-3/2x=5/12`
`=>-5/6x=5/12`
`=>x=-1/2`
Vậy `x=-1/2`
2/3x-3/2x=5/12
x.(2/3-3/2)=5/12
x.-5/6 =5/12
x =5/12:-5/6
x =-1/2
`2/3x-3/2x=5/12`
`=>-5/6x=5/12`
`=>x=-1/2`
Vậy `x=-1/2`
2/3x-3/2x=5/12
x.(2/3-3/2)=5/12
x.-5/6 =5/12
x =5/12:-5/6
x =-1/2
\(a,\left(\dfrac{37}{9}+\dfrac{13}{4}\right)x\dfrac{9}{4}+\dfrac{11}{4}\) b,\(1+\left(\dfrac{9}{10}-\dfrac{-4}{5}\right):\dfrac{19}{6}\)
c,\(\dfrac{1}{4}-\dfrac{3}{2}+\dfrac{1}{2}x\dfrac{12}{5}\)
Giúp mik nha:>
Tìm x, biết:
a) \(\dfrac{3}{4}x\) - \(\dfrac{7}{12}\) = \(\dfrac{5}{6}\) - \(\dfrac{2}{3}\)
b) -\(\dfrac{5}{x}\) = \(\dfrac{20}{28}\)
c) \(2\dfrac{1}{3}\) : x = 7
d) \(\dfrac{-105}{12}\) < x < \(\dfrac{20}{7}\)
x \(\dfrac{2}{3}\)=\(\dfrac{1}{5}\)
\(\dfrac{2}{x}\)=\(\dfrac{12}{5}\)
\(\dfrac{1}{2}\)x-\(\dfrac{3}{5}\)=\(\dfrac{-4}{5}\)
3x+2x=-5,05
tìm x biết
a , \(\dfrac{-3}{10}\)-(\(\dfrac{-1}{5}\) +x)=\(\dfrac{-3}{2}\)
b, -(-x+ \(\dfrac{3}{4}\))- \(\dfrac{12}{8}\).- \(\dfrac{32}{15}\)=- \(\dfrac{-1}{2}\)
c, \(\dfrac{x-3}{x+5}\)=\(\dfrac{4}{3}\)
tìm x
\(\dfrac{3-x}{5-x}=\dfrac{6}{11}\) \(\left(1\dfrac{1}{3}-25\%.x-\dfrac{5}{12}\right)-2x=1,6:\dfrac{3}{5}\)
\(\dfrac{1}{2}.\left(x-\dfrac{2}{3}\right)-\dfrac{1}{3}.\left(2x-3\right)=x\)
\(2.\left(\dfrac{1}{2}-x\right)-3\left(x-\dfrac{1}{3}\right)=\dfrac{7}{2}\)
tìm x biết
a)x-\(\dfrac{3}{7}\)=\(\dfrac{2}{5}.\dfrac{1}{4}\)
b)x+\(\dfrac{4}{5}\)=\(\dfrac{-5}{12}\).\(\dfrac{3}{25}\)
c)\(\dfrac{x}{182}\)=\(\dfrac{-6}{12}\).\(\dfrac{35}{91}\)
Tìm x, biết:
a) x+\(\dfrac{1}{6}\)=\(\dfrac{-3}{8}\) b) \(2-\left(\dfrac{3}{4}-x\right)=\dfrac{7}{12}\)
c) \(\dfrac{1}{2}x\)+\(\dfrac{1}{8}x=\dfrac{3}{4}\) d) 75%-\(1\dfrac{1}{2}+0,5:\dfrac{5}{12}-\left(\dfrac{-1}{2}\right)^2\)
tim x
\dfrac{5}{6}x-\dfrac{3}{4}=\dfrac{-1}{4}+\dfrac{2}{3}65x−43=4−1+32
-1\dfrac{1}{2}-\dfrac{2}{3}x=\dfrac{5}{6}-\left(\dfrac{-2}{5}\right)−121−32x=65−(5−2)
\left(\dfrac{4}{5}:x+1,5\right):\dfrac{2}{3}=-1,5(54:x+1,5):32=−1,5
\dfrac{4}{3}x-\dfrac{2}{3}=\dfrac{1}{4}-x34x−32=41−x
giup minh nhe minh dang can gap
*Thực hiện
1/ (\(\dfrac{2021}{2020}\)+\(\dfrac{2020}{2021}\)) x (\(\dfrac{1}{2}\)-\(\dfrac{1}{3}\)-\(\dfrac{1}{6}\))
2/ (\(\dfrac{7}{19}\)-\(\dfrac{5}{12}\)):\(\dfrac{-5}{8}\)-(\(\dfrac{7}{19}\)-\(\dfrac{29}{12}\)):\(\dfrac{5}{8}\)
3/ \(\dfrac{-5}{6}\)x\(\dfrac{7}{24}\)-\(\dfrac{5}{6}\)x\(\dfrac{14}{24}\)-\(\dfrac{5}{6}\)x\(\dfrac{3}{24}\)